2018
DOI: 10.25186/cs.v13i1.1388
|View full text |Cite
|
Sign up to set email alerts
|

Competitive Pressures on the Artisan Coffee Roaster Segment in the State of Minas Gerais, Brazil: A Multi-Case Study

Abstract: ABSTRACT:The specialty coffee market is still little known and underexplored in Brazil, motivating an analysis of the competitive pressures and structure of the artisan coffee roaster segment in the state of Minas Gerais, in order to better understand it and encourage the adoption of specific policies for its expansion, besides comparing it to the commodity coffee roasting segment. A multi-case study was performed with three companies in this segment through in-depth interviews with their owners. There were si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 6 publications
0
2
0
1
Order By: Relevance
“…Robusta coffee is a shallow‐rooted crop that requires frequent doses of fertilizers coupled with soil moisture to utilize nutrients more effectively. Oliveira et al (2006) and Guimaraes et al (2010) reported that providing irrigation water directly into soil at the root zone of plants through drip not only minimized conventional losses, such as deep percolation, runoff and soil erosion, but also resulted in substantial fertilizer savings. In the present study, drip irrigation (fertigation) was applied in 65 different splits, while various concentrations (75%, 100%, 125% and 150%) of fertilizers were applied through soil application in two splits.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Robusta coffee is a shallow‐rooted crop that requires frequent doses of fertilizers coupled with soil moisture to utilize nutrients more effectively. Oliveira et al (2006) and Guimaraes et al (2010) reported that providing irrigation water directly into soil at the root zone of plants through drip not only minimized conventional losses, such as deep percolation, runoff and soil erosion, but also resulted in substantial fertilizer savings. In the present study, drip irrigation (fertigation) was applied in 65 different splits, while various concentrations (75%, 100%, 125% and 150%) of fertilizers were applied through soil application in two splits.…”
Section: Discussionmentioning
confidence: 99%
“…Robusta coffee is a shallow-rooted crop that requires frequent doses of fertilizers coupled with soil moisture to utilize nutrients more effectively. Oliveira et al (2006) and Guimaraes et al (2010) 2010) reported that nutrient use efficiency could be as high as 90% in fertigation compared to 40%-60% in conventional methods of fertilizer application, and the amount of nutrients lost through leaching can be as low as 10% in fertigation, whereas it is 50% in the traditional system. Furthermore, studies on fertigation have revealed significant fertilizer savings of 20%-60% and 8%-41% increases in yields in horticultural and vegetable crops (Singh & Singh, 2021).…”
Section: Fertilizer Use Efficiencymentioning
confidence: 99%
“…Metode ini melibatkan pengawasan ketat terhadap suhu, waktu, dan aliran udara selama pemanggangan, mengembangkan profil rasa yang mendalam. Pendekatan ini memungkinkan variasi rasa, mulai dari keasaman cerah hingga kekentalan kaya [17]. Seni pemanggangan ini akan membuat kopi Probolinggo berbeda di pasar yang kompetitif, serta menarik bagi konsumen modern yang mencari kualitas dan variasi rasa.…”
Section: Meningkatkan Kualitas Cita Rasa Kopi DIunclassified